Quasi-fideist Presuppositionalism: Cornelius Van Til, Wittgenstein, and Hinge Epistemology - Smith, Nicholas (Philosophia reformata, 2023)
I argue that the epistemology underlying Cornelius Van Til’s presuppositional apologetic methodology is quasi-fideist. According to this view, the rationality of religious belief is dependent on absolutely certain ungrounded grounds, called hinges. I further argue that the quasi-fideist epistemology of presuppositional apologetics explains why Van Til’s method is neither fideist nor problematically circular: hinges are rational in the sense that they are partly constitutive of rationality, and all beliefs (not just religious ones) depend on hinges. In addition, it illuminates something of why it may strike one as a misguided or uncompelling apologetic method: instead of starting by tackling the comparatively minor epistemic commitments of the nonbeliever, it directly approaches their deepest and surest commitments.